CLIMATE CHANGE: A THREAT TO NATIONAL SECURITY OF PAKISTAN - Muhammad Aslam; Saqib Hussain; Sultan Salah-ud-Din (International Journal of Contemporary Issues in Social Sciences, 2024)
Climate change has emerged as a major nontraditional security concern for the global community. It has a greater impact on developing countries Pakistan, which is now the eighth-most climate-vulnerable nation, is suffering the most. Climate change-related disasters such as floods, heatwaves, droughts, glacier melting, and sea-level rise have caused massive economic and human losses in Pakistan. As a result, it has weakened Pakistan's economic, food, human, and environmental security, thereby jeopardizing the country's national security. The purpose of this research is to look into how climate change is threatening Pakistan's national security. This study employed analytical and explanatory methodology, as well as qualitative analysis of primary and secondary materials. Floods, droughts, and heatwaves have not only destroyed Pakistan's agriculture sector, but have also resulted in other human and material losses. This has resulted in significant economic, food, and human security losses in Pakistan, undermining the country's national security. National security includes military, economic, human, food, cyber, and environmental safeguards. If any of these is jeopardized, the country's national security is jeopardized. Climate change has resulted in significant losses in almost all of these national security components, posing a serious threat to the national security of Pakistan.